Granulocyte–macrophage colony‐stimulating factor (GM‐CSF) as a therapeutic target in psoriasis: randomized, controlled investigation using namilumab, a specific human anti‐GM‐CSF monoclonal antibody. (1st June 2019) - Papp, K.A.; Gooderham, M.; Jenkins, R.; Vender, R.; Szepietowski, J.C.; Wagner, T.; Hunt, B.; Souberbielle, B.; ,
Summary: Background: The relevance of granulocyte–macrophage colony‐stimulating factor (GM‐CSF) in the management of psoriasis has not been studied previously. GM‐CSF is important in the initiation and maintenance of chronic inflammatory processes. Objectives: To investigate the clinical use of GM‐CSF neutralization by evaluating the efficacy and safety of namilumab (AMG203), a monoclonal antibody GM‐CSF inhibitor, in patients with moderate‐to‐severe plaque psoriasis. Methods: A phase II, multicentre, randomized, double‐blind, placebo‐controlled, parallel‐group, dose‐finding, proof‐of‐concept study (NEPTUNE) was conducted. Four doses of namilumab (20, 50, 80 and 150 mg, via subcutaneous injection) were compared with placebo. Assessment of the primary end point – the proportion of patients achieving ≥ 75% reduction in Psoriasis Area and Severity Index (PASI 75 treatment response) – was performed at week 12. Exploratory investigation at the tissue level was conducted in a subset of the overall study population. The trial was registered with the number NCT02129777. Results: In total, 122 patients were enrolled and 106 (86·9%) completed the double‐blind treatment; 16 (13·1%) prematurely discontinued study medication. Serum concentration–time profiles were as expected for subcutaneous delivery of an IgG1 monoclonal antibody, and exposure increased proportionally with dose elevation. The number of patients showing PASI 75 treatment response at week 12 was low in all groups; no significant difference was recorded in this end point between placebo and any namilumab group. Similar outcomes were recorded for other clinical study end points. Moreover, no significant treatment‐related changes from baseline were observed in laboratory investigations of cell types or subpopulations, or cytokines relevant to inflammatory pathways in psoriasis. Conclusions: GM‐CSF blockade is not critical for suppression of key inflammatory pathways underlying psoriasis.